The Influence of Work Ability, Work Discipline and Work Environment on Employee Performance - Dewa, Adenanthera (LifeSciFi, 2023)
Work ability is one of the problems that occurs almost throughout the world which requires serious handling considering that it greatly influences employee performance factors. The aim of this research is to analyze the influence of the independent variable on the dependent variable. With a population of all employees at the Steam Power Plant (Pembangkit Listrik Tenaga Uap or PLTU) Tanjung Jati B Jepara and a sample of 110 respondents was taken. With a simple random sampling type probability sampling technique, data collection uses a questionnaire, the data analysis technique used is multiple regression analysis techniques including validity testing, reliability testing, classical assumption testing, and hypothesis testing. From the research results, there is a relationship between the independent variable and the dependent variable. Hypothesis testing using the t test shows that the three independent variables, namely work ability, work discipline, work environment, which were studied were proven to have a positive and significant effect on the dependent variable. namely the employee performance factor, with the work ability variable having the highest influence than the other variables in influencing employee performance factors, hypothesis testing using the f test shows that the three independent variables simultaneously have a positive and significant effect on the employee performance. In addition, 60% of the variation in the dependent variable of employee performance factors can be explained by the independent variables of work ability, work discipline and work environment. Meanwhile, the remaining 40% is explained by other causes outside the variables.